Impacts of short-term measures to decarbonize maritime transport on perishable cargoes - Zis, Thalis; Psaraftis, Harilaos N. (My University, 2021)
The International Maritime Organization (IMO) has adopted a strategy to reduce emissions from international shipping that sets very ambitious targets. The first set of actions, so-called short-term measures, are expected to be implemented by 2023 and result in a reduction of emission intensity by at least 40% by 2030 compared with 2008 levels. Compliance may be achieved through a reduction in sailing speeds, but certain countries have raised concerns on the ramifications of longer transit times on their exports, particularly for perishable products. In this paper, we present a methodology to assess the impacts of various short-term measures on perishable products. We use an extension of a nested modal split model to examine shifts towards other modes of transport. We demonstrate our methodology with a transpacific case study carrying perishable products from South America to China. We compare the short-term measures currently under discussion, in one of the first academic studies to explore these issues. These include a speed limit approach, a power limit, and a goal-based measure. Our results show that a power limit or a goal-based measure would offer some advantages to liner shipping operators using more efficient vessels, unlike a speed limit. Using 2008 as the benchmark year has resulted in small speed reductions required by the liner shipping sector to reach its targets. For perishable cargoes, small speed reductions can be tolerated by the shippers without significant modal shift. Choosing the right short-term strategy is of utmost importance to promote clean shipping practices in the following years.
Keywords: transpacific; trade; decarbonization of shipping; emissions intensity; perishable cargoes; modal shift